2020
DOI: 10.1155/2020/8498401
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of an Unusual Salter-Harris Type IV Fracture of the Ulna

Abstract: We report the case of a 14-year-old boy with an isolated Salter-Harris type IV physeal fracture of the distal ulna. Following failed closed reduction, transition to open reduction and pin fixation was required. Six-month follow-up showed a favourable clinical evolution. Evidence suggests that long-term follow-up is needed because of the increased risk of premature physeal closure and subsequent growth disturbances associated with this type of injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 17 publications
0
11
1
Order By: Relevance
“…In a review of 163 physeal fractures of the distal forearm, only six ulnar physeal fractures were found, and just one was isolated (Cannata et al, 2003). We found only two cases of isolated SH Type IV ulnar fractures previously reported (Kasis et al, 2004;Marrannes et al, 2020). In these cases, a single Type IV fracture pattern was present, as opposed to the more complex double line fracture configuration, observed in our patient.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…In a review of 163 physeal fractures of the distal forearm, only six ulnar physeal fractures were found, and just one was isolated (Cannata et al, 2003). We found only two cases of isolated SH Type IV ulnar fractures previously reported (Kasis et al, 2004;Marrannes et al, 2020). In these cases, a single Type IV fracture pattern was present, as opposed to the more complex double line fracture configuration, observed in our patient.…”
contrasting
confidence: 55%
“…In a case of SH Type IV ulna fracture (with concomitant radius fracture), O'Hagan et al ( 2012) placed two longitudinal K-wires, traversing the growth plate. Kasis et al (2004) and Marrannes et al (2020) placed three wires parallel to the growth plate (two divergent wires in the epiphyseal segment plus one in the metaphyseal segment). Marrannes et al used an anterior approach as opposed to our dorsal approach.…”
mentioning
confidence: 99%
“…Cannata et al, in a long-term, follow-up study, reported five such fractures in combination with distal radial metaphyseal fractures, but only one isolated ulnar injury, in a sample of 163 patients [ 3 ]. During our extensive literature research, we were able to identify only five cases, two of which were classified as Salter-Harris type IV, one as type III, and two as type II [ 4 - 8 ] (Table 1 ). In all five cases, the mechanism of injury was described as a fall on the outstretched hand from either a bike or a motorcycle, which is similar to the presented case.…”
Section: Discussionmentioning
confidence: 99%
“…Zimmermann et al reported negative ulnar variance in 10% of patients during a long-term study of more than 200 distal forearm fractures [ 15 ]. A high percentage of premature epiphyseal plate closure also derives from the analysis of the five published cases as in three of them a negative ulnar variance was observed during follow-up [ 4 , 5 , 8 ]. As stated before, this complication is basically explained by the fact that the distal physeal plate of the ulna accounts for 70-80% of ulnar growth, so fractures in the area may lead to axial shortening of the ulna.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation